OPTIMALISASI DESTINATION BRANDING MELAUI MEDIA PROMOSI DESA WISATA CIKOLELET - Rahmat, Lintang; Primasari, Intan (Ilmu Komunikasi, FISIP Universitas Pasundan, 2024)
ABSTRACT Promotional media is a communication tool in conveying information and has an important role in the tourism sector so as to increase public interest in visiting a destination based on information obtained from various media, such as articles, social media, etc. Therefore, promotional media management is related to optimizing the branding destination of the Cikolelet Tourism Village. The local government seeks various aspects of media attention in promoting the Cikolelet Tourism Village as a leading tourist destination in Serang Regency. The aim of this research is to determine the management of destination branding and promotional media used in an effort to optimize the well-formed destination branding of the Cikolelet Tourism Village. This research uses a qualitative descriptive research method which describes the phenomena that occur using the constructivist paradigm in order to examine the science between phenomena that occur in the field with theory and previous research as a reference in implementing the practice of using promotional media and its implications. The results of this research describe the implementation of promotional media management as a tool to support destination branding in the Cikolelet Tourism Village. The promotional media used and managed in optimizing the Cikolelet Tourism Village, both by the local government and tourist attraction managers, use mass media such as newspapers, radio and television as well as digital media such as social media and websites and online media reporting. Keywords: Destination Branding, Promotional Media, Tourism Village